Estimating the cost of young stock mortality in livestock systems—An application to sheep farming in Ethiopia - Otte, Joachim; Schnier, Christian; Allan, Fiona K.; Salmon, Gareth; Wong, Johanna T.; Minjauw, Bruno (Frontiers in Veterinary Science, 2024)
In sub-Saharan Africa, pre-weaning young stock mortality (YSM) ranges from 20 to 30 percent, posing significant economic challenges for livestock keepers. However, few studies have quantified the actual cost of YSM. This study employs a bio-economic herd modeling approach to estimate this cost. Using the static zero-growth version of DYNMOD, the study assessed the annual physical and monetary output of a 100-breeding-female sheep flock at various levels of lamb mortality. Calculations were conducted from 30% to 0% mortality in 5% intervals, with 20% considered baseline YSM. Additionally, scenarios with high fertility rates were explored to understand sensitivity to productivity changes. The analysis reveals a near-linear relationship between revenue per head and YSM, with a 1% decrease in YSM leading to approximately a 1% increase in revenue per animal. Under higher fertility rates, the absolute cost of YSM is greater, though the relative increase in revenue per animal from YSM reduction is lower. The study estimates that reducing lamb mortality from 20% to 0% could yield approximately USD 90 per additional surviving lamb, well surpassing its market value. This increase in revenue stems from higher sales of mature animals, incorporating both the initial value of the lamb and the profit from raising it to marketable age/weight. The modelling results suggest that foregone profit is an important component of the ‘cost of YSM’. Consequently, expected profit per animal, rather than its current market value, is essential for estimating the absolute cost of YSM.